2013
DOI: 10.5336/medsci.2012-30385
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Special Amino Acid Mixture on Healing of Left Colonic Anastomosis: an Experimental Study

Abstract: A AB BS ST TR RA AC CT T O Ob bj je ec ct ti iv ve e: : Arginine, glutamine, and Beta-hydroxy-beta-methylbutyrate were combined in a dietary supplement. This specialized amino acid mixture enhances wound collagen accumulation and increases wound healing. We aimed to investigate the effects of this special amino acid mixture on the healing process of experimental left colonic anastomosis. M Ma at te er ri ia al l a an nd d M Me et th h--o od ds s: : The study included 20 adult male Wistar-Albino rats. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 22 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…This study, by Kusabbi and colleagues (2015) [ 33 ], investigated the effect of an oral nutritional supplement containing AGHMB on anastomotic healing in rats. Other groups that investigated the effect of AGHMB on anastomotic healing found a similar effect on neovascularization and fibroblast proliferation 7 days postoperative (Akbulut et al, 2019) [ 29 ], and saw an increase in reepithelialisation (Yaman et al, 2012) [ 40 ]. Reepithelialisation of necrotic ulcers at the suture line, and deeper crypts, were also major findings in the study by Aguilar and colleagues (1997) [ 28 ] into the effects of intraoperative SCFA lavage on anastomotic healing in rats with colonic obstruction (IAH).…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…This study, by Kusabbi and colleagues (2015) [ 33 ], investigated the effect of an oral nutritional supplement containing AGHMB on anastomotic healing in rats. Other groups that investigated the effect of AGHMB on anastomotic healing found a similar effect on neovascularization and fibroblast proliferation 7 days postoperative (Akbulut et al, 2019) [ 29 ], and saw an increase in reepithelialisation (Yaman et al, 2012) [ 40 ]. Reepithelialisation of necrotic ulcers at the suture line, and deeper crypts, were also major findings in the study by Aguilar and colleagues (1997) [ 28 ] into the effects of intraoperative SCFA lavage on anastomotic healing in rats with colonic obstruction (IAH).…”
Section: Resultsmentioning
confidence: 87%
“…In case there was any mentioning of blinding (7 studies, 37%), this usually concerned blinding of an outcome assessor handling the histologic evaluation. Only one study [ 40 ] explicitly mentioned blinding for all outcomes. None of the studies reported power/sample size calculations to justify their experimental group sizes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations